Clinical Application of the PES/WES Index on Natural Teeth: Case Report and Literature Review - Alessandro Lanza; Fabrizio Di Francesco; Gennaro De Marco; Felice Femiano; Angelo Itro (Hindawi Limited, 2017)
The use of reliable indices to evaluate the aesthetic outcomes in the aesthetic area is an important and objective clinical aid to monitor the results over time. According to the literature various indices were proposed to evaluate aesthetic outcomes of implant-prosthetic rehabilitation of the anterior area like Peri-Implant and Crown Index [PICI], Implant Crown Aesthetic Index [ICAI], Pink Esthetic Score/White Esthetic Score [PES/WES], and Pink Esthetic Score [PES] but none of them was related to prosthetic rehabilitation on natural teeth. The aim of this study is to verify the validity of PES/WES index for natural tooth-prosthetic rehabilitation of the anterior area. As secondary objective, we proposed to evaluate the long-term predictability of this clinical application, one of which is presented below, following the analysis of the most currently accepted literature.